Differential Role of Factor XIII in Acute Myocardial Infarction and Ischemic Stroke - Jan Traub; Martin S. Weber; Anna Frey (Biomedicines, 2024)
Factor XIII is a transglutaminase enzyme that plays a crucial role in hemostasis and wound healing. It crosslinks fibrin strands, stabilizing clots and promoting clot resistance to fibrinolysis. Additionally, Factor XIII has been found to have multiple other functions that extend beyond coagulation, including the regulation of inflammation and tissue repair processes. Emerging evidence suggests that Factor XIII may also have differential roles in acute myocardial infarction and ischemic stroke, two common cardiovascular events with significant morbidity and mortality. In acute myocardial infarction, Factor XIII has been implicated in promoting clot stability and reducing the risk of re-occlusion. In ischemic stroke, Factor XIII may also contribute to the pathogenesis of cerebral ischemia by promoting clot formation and exacerbating neuronal damage. Several studies have investigated the association between Factor XIII and these cardiovascular events, using various approaches such as genetic polymorphism analysis, animal models, and clinical data analysis. These studies have provided important insights into the role of Factor XIII in acute myocardial infarction and ischemic stroke, highlighting its potential as a therapeutic target for interventions aimed at improving outcomes in these conditions. In this review, we will summarize the current understanding of Factor XIII’s role in acute myocardial infarction and ischemic stroke.